Development of a Fast, Sensitive and Robust LC-MS/MS Method for the Analysis of Natamycin in Wine - Alberts, P.; Stander, M.A.; de Villiers, A. (South African Journal of Enology and Viticulture, 2011)
Natamycin is a naturally occurring antifungal agent used to inhibit the growth of moulds and yeasts. Characteristics such as low effective concentrations, broad applicability and neutral flavour impact make this compound an ideal preservative. Although widely used in the global food industry, natamycin is forbidden in wine in the European Union (EU). It is a permitted wine additive in South Africa, although export wines must comply with EU standards. Germany in particular implemented strict measures to prevent wines containing natamycin from entering their market. Sensitive analytical methodologies with the capacity to regulate this segment of the wine export industry are therefore required. Here we report on the development of a simple, robust and fast liquid chromatography-electrospray ionisation tandem mass spectrometric (LC-ESI-MS/MS) method for the determination of natamycin in wine. Sample cleanup involves dilution followed by direct elution of natamycin from aminopropyl SPE cartridges. Recoveries are better than 80% relative standard deviation (RSD < 10%), while the limit of detection (LOD) of the method is 0.0003 mg/L, which renders it compliant with EU standards. The method also yields qualitative information for positive compound identification. The degradation of natamycin in wine was also studied and kinetic parameters are reported in this matrix for the first time. The activation energy for the decomposition reaction is ~80 kJ/mol and the half-life under normal wine storage conditions is in the order of 20 days. As in the wine matrix, natamycin in aqueous calibration standards are labile, necessitating regular preparation and cold storage of standard solutions to ensure accurate quantitation.